Education and training needs assessment of Diocesan archives and records management personnel - De la Paz, Lea M.; Santos, Herminia H.; Arlante, Salvacion M.; Granda, Yolanda C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2001)
Record-keeping in the Roman Catholic Church in the Philippines dates back hundreds of years to the Spanish period. A sizable number of the permanent records created during that period still exist in diocesan curiae and parishes. These are considered by the Church as its archival heritage. The physical preservation of the documents, the information these contain and the dissemination of their use is left to the hands of the present-day diocesan personnel, namely: the chancellors, parish priests and lay ecclesiastical personnel. A similarly important task is the management of records. Since records-keeping and the administration of archives are only part of the responsibilities of the chancellors, parish priests and lay ecclesiastical personnel, this research was carried out in order to determine whether they have received training for the job, in which areas they should still receive training on and whether current education and training programs are able to answer their education and training needs.
Fifty-six respondents were personally visited for an interview and observation, equally divided into 28 priests and 28 ecclesiastical personnel, belonging to 29 parishes in 7 dioceses in Luzon and Visayas. Priests and lay ecclesiastical personnel have a low level of pre-service education on records management and archives administration. Post-appointment training is also low resulting to non-performance of the full range of activities involved in records management and archives administration.
Formal courses from several universities were compared and analyzed. The topics of selected training programs of private and government institutions and professional associations were compared and analyzed to the extent that these are able to answer the education and training needs of diocesan personnel. As a result of the interview conducted, observations made, and analyses of the education and training programs, several modules were suggested separately for the pre-service professional education and post-appointment training of diocesan archives and records management personnel.
Vita.
Thesis (Master of Library Science)--University of the Philippines Diliman
Keywords: Archives, Diocesan--Employees--Training of--Philippines.; Archives, Diocesan--Philippines--Employees.; Church records and registers--Philippines.